Preanalytical classical and alternative complement pathway activity loss - Vercauteren, Koen O. A. (Array, 2019)
Complement functional analyses provide insight into the integrity of the entire complement reaction cascade. These tests are suitable for investigating suspected complement deficiencies. Falsely reduced test outcomes may result from preanalytical instabilities of individual complement components. To generate rationale for this or potential alternative practices, this study aimed to extend the knowledge on the preanalytical stability of widely used tests to screen the complement system. We assessed the influence of time, temperature and EDTA on classical (CH50) and alternative pathway (AP50) functional assay test results.Materials and methods: We used nephelometric (C3d) and immunofixation (C3c) techniques to support the investigation of the preanalytical phase of basic complement system activity tests. Quantitative determination of classical and alternative pathway function was performed with a haemolytic activity assay and a C5b-9 neo-epitope ELISA-based assay respectively. Blood of five healthy volunteers was sampled and complement components allowed to degrade under different conditions.Results: CH50 and AP50 remain stable for approximately one week in serum samples incubated on ice. CH50 activity decreased almost twice as fast in EDTA plasma compared to serum at room temperature. AP50 activity contrastingly, decreased twice as slow in EDTA plasma compared to serum at room temperature.Conclusion: Serum on ice remains the preferred specimen for functional complement analyses. In the absence of serum transported on ice, serum kept at room temperature (not exceeding 24h) is suitable for classical and alternative pathway analyses. For alternative pathway analyses specifically, the C3-stabilising effect of EDTA allows for the extended use of EDTA plasma (not over 4 days). In these conditions, at least 85% of baseline complement activity remains.